Can we repeat what we do not say in L2? - Ramonaitė, Jogilė Teresa (Taikomoji kalbotyra, 2021)
The paper analyzes the results of a sentence repetition task performed by Lithuanian L2 speakers of different language proficiency levels. This paper focuses on a set of targeted verb forms included in the task because they are less likely to occur in free production. The different forms the speakers produced are analyzed by considering their correspondence (or not) to the targeted form, by comparing the speakers among each other with respect to their learner variety and by comparing the task results to the repertoire of the same speaker in the free production data. In multiple cases of failed re-production, the analysis examines what the targeted forms were substituted with and tries to identify possible reasons for such substitution. This analysis confirms the general inability of the basic variety speakers to distinguish between morphologically different forms and the dominant trend showing that L2 learners are more meaning-focused than form-focused. The analysis also shows growing implicit knowledge, or at least gradual passive acquisition, of the less frequent forms as the speaker advances in the post-basic continuum.
Keywords: Lithuanian L2; implicit language knowledge; sentence repetition task; acquisition of morphology; verb morphology